Ecological Flow of Intensively Developed and Utilized Rivers in Yunnan Province Based on Improved Tennant Method - LI Jiao; LI Xuehui (Renmin Zhujiang)
The ecological flow of rivers is the basic element for maintaining a river ecosystem and an important indicator for controlling the intensity of water resource development and utilization.Studying ecological flow is a significant part of endorsing river health.According to the characteristics of the intensively developed and utilized rivers in Yunnan Province,this paper takes the Niulan River system in the Jinsha River Basin as a representative to carry out ecological flow research.It proposes an improved Tennant method according to the division of the river's “water use period”,“flood control period”,and “water storage period” and compares it with three common hydrological methods.According to the comparison,the proposed improved Tennant method has obvious advantages in meeting the water use characteristics of rivers in development and utilization,the variation law of natural rivers' abundance and dryness throughout the year,the ecological environment conditions in the river course,and the ecological flow satisfaction rate in dry seasons.